Investigation of leptin receptor rs1137101 G>A polymorphism with cancer risk: evidence from 35936 subjects. Issue 6 (28th June 2019) - Rong, Guoxiang; Tang, Weifeng; Wang, Yafeng; Qiu, Hao; Chen, Shuchen
Abstract : Leptin receptor (LEPR) signaling may be involved in promoting angiogenesis and proliferation, inhibiting apoptosis and playing a vital role in the progression of carcinogenesis. A number of studies have focused on the association of LEPR rs1137101 variants with susceptibility of cancer, however, the observed results were controversial. We searched literature on the relationship of LEPR rs1137101 G>A polymorphism with cancer risk by using PubMed and Embase databases, covering all publications up to 14 October 2018. In total, 44 case–control studies with 35, 936 subjects were included. After combining all eligible studies, we identified null relationship between LEPR gene rs1137101 G>A polymorphism and overall cancer risk [A vs. G: odds ratio (OR ) =  0.97, 95% confidence interval (CI ) =  0.89–1.06, P  = 0.547; AA vs. GG: OR  =  0.93, 95% CI  =  0.78–1.13, P  = 0.476; AA/GA vs. GG: OR  =  0.99, 95% CI  =  0.91–1.09, P = 0.890 and AA vs. GA/GG: OR  = 0.92, 95% CI  =  0.82–1.04, P = 0.198]. However, in a subgroup analysis, there was an increased susceptibility of oral and oropharyngeal cancer in AA vs. GA/GG genetic model (OR, 1.83; 95% CI, 1.01–3.33; P =0.048). Considering the limited participants were included, the findings might be underpowered. Sensitivity analysis identified that any independent study omitted did not materially influence the pooled ORs and CIs. The results of publication bias detection showed that there was no evidence of bias. In summary, this analysis indicates that no significant association of cancer risk was identified to be correlated with rs1137101 G>A variants, even in stratified analyses.